PENGARUH KOMPETENSI, INDEPENDENSI, DAN ETIKA TERHADAP KUALITAS AUDITOR PADA APARAT INSPEKTORAT DALAM PENGAWASAN PENGELOLAAN KEUANGAN DAERAH KOTA BITUNG - Maramis, Lidya Anggiline; Wokas, Heince (ACCOUNTABILITY, 2013)
The increasing demands of the community for clean governance, fair, transparent, andaccountable should be taken seriously and systematically. All levels of state officials, both at the level of the executive, legislative, and judicial branches must have a shared commitment to uphold good governance and clean government. The study was conducted in the supervision of Government Internal City officials in this regard Inspectorate Bitung in Bitung City. In the present study investigated the influence of competence, independence and ethics for auditors in monitoring the quality of financial management. The purpose of research is to determine how much influence the competence, independence, and ethics to the quality of the personnel inspectorate auditors in financial management oversight Bitung City.Data analysis methods used are descriptive statistics, the classical assumption test, test correlation coefficient, coefficient of determination t est, hypothesis testing  ( test f and t test ) . to complete the overall data analysis used SPSS software version 20. The results showed the equation Y = 6.882 -0.019 + 0.437 X1 0.300 X2 + X3. Of multiple linear regression equation shows a constant value of 6.882 gives the sense that if competence  ( X1) , independence  ( X2 ) , and ethics  ( X3 )  constant perceived or equal to zero  ( 0 ) , then the magnitude of the variable quality of the auditor on the apparatus inspectorate  ( Y )  amounted to 6.882. Correlation coefficient obtained for the coefficient of determination of 0.700 and 0.490, while the remaining 51% of other variables not examined in this study. Results of hypothesis testing  ( test f )  indicates the level of significance is less than 0.05 is 0.000 thus, the study received HA4 hypothesis, and hypothesis testing  ( t test )  showed for the variable  ( X1 )  = 0.864 competence as such, this study rejected Ha1 hypothesis which states that competency variable does not affect the quality of the auditors, it can be seen from a greater significance level of 0.05 is 0.864. These results contrast with previous research that states that affect the quality of the auditor's competence. This is due to the lack of training in research or no education system appropriate competency and followed by the Inspectorate in the auditor oversight of financial management in the city of Bitung,  ( X2)  = 0.05 ie 0.001 independence as such, this study received a hypothesis Ha2, and  ( X3 )  = 0.05 ie 0.008 ethics as such, this study received Ha3 hypothesis.